The Influence of the Application of Audio Visual Learning Media in Increasing the Religious and Moral Value of Children Aged 5-6 Years in Adabiah Kindergarten, Padang City - Yessi Rifmasari (Faculty of Teacher Training and Education, Universitas Terbuka, 2021)
The research was motivated by the low development of religious and moral values (NAM) of children aged 5-6 years at Adabiah Kindergarten in Padang City. Judging from the development of NAM many children who have not been able to know religion and religious holidays. The research aims to determine the Effect of The Application of Audio Visual Learning Media in Improving NAM Children Aged 5-6 Years. This type of research is quasai experimental desaign. Population of all children Aged 5-6 years, selected samples of grades B1 and B2. Sampling techniques using purposive sampling techniques, using the t-test formula. Analysis of normal and homogeneous distributed data, then conducted hypothetical tests with t-test showed obtained . thitung >ttabel (2,301 > 2,048), then Ho was rejected and Ha accepted. Conclusion